Indonesian Language for Foreign Speakers: A Political Strategy Of Indonesian Language To Go International - Defina; Krishandini (Universitas Pakuan, 2025)
The significance of this writing lies in its exploration of the political process of the Indonesian language, a crucial step in making Indonesian an international language. Internationalizing Indonesians is a key area of study in our research. This qualitative descriptive research uses data collection techniques through a literature study. Indonesian language politics began: (1) in 1917, with the establishment of Balai Pustaka, (2) in 1928, through the Youth Pledge, (3) the First Indonesian Language Congress in 1938, (4) in 1945 through the 1945 Constitution to language regulations, (5) a series of II-XII Indonesian Language Congresses 1954-2023, (6) a series of changes in Indonesian spelling from Van Ophuijsen to the perfected spelling (EYD V) in 1901-2022, (7) The V Indonesian Language Congress (1988) initiated the process of internationalizing the Indonesian language through BIPA (Indonesian Language for Foreign Speakers) until the formation of the APPBIPA organization. Our research has uncovered a unique connection: the internationalization of Indonesian is intricately linked to the transformation of Malay into Indonesian before the independence of the Republic of Indonesia. Our research fills a significant gap in the literature. There has been no comprehensive study on the long journey of internationalization of the Indonesian language, from pre-independence to recognizing Indonesian as one of the languages ​​of instruction at UNESCO. Keywords: BIPA, international language, internationalization of Indonesian, Malay language, political language